2017
DOI: 10.1001/jamaneurol.2016.5131
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Architecture and Melanopsin-Mediated Pupillary Response Characteristics

Abstract: IMPORTANCE A neurophysiologic signature of the melanopsin-mediated persistent constriction phase of the pupillary light reflex may represent a surrogate biomarker for the integrity of the retinohypothalamic tract, with potential utility for investigating alterations in homeostatic mechanisms associated with brain disorders and implications for identifying new treatments.OBJECTIVE To characterize abnormalities of retinal architecture in patients with multiple sclerosis (MS) and corresponding alterations in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 46 publications
0
22
0
Order By: Relevance
“…Two other studies found seasonal differences: one study of a mixed group of healthy and depressed adults showed greater PIPR in summer ( 42 ), and another study of SAD patients had lower PIPR only in winter when compared with controls ( 46 ). The distinction whether a larger PIPR indicates greater melanopsin-dependent light sensitivity is important and a common methodological consensus will be needed if the pupil is targeted to be a biomarker of pathology such as seasonal depression or multiple sclerosis ( 42 , 72 ). Taken together it might be that various other processes related to opsin regulation have variable influence on changes in seasonal light responses.…”
Section: Discussionmentioning
confidence: 99%
“…Two other studies found seasonal differences: one study of a mixed group of healthy and depressed adults showed greater PIPR in summer ( 42 ), and another study of SAD patients had lower PIPR only in winter when compared with controls ( 46 ). The distinction whether a larger PIPR indicates greater melanopsin-dependent light sensitivity is important and a common methodological consensus will be needed if the pupil is targeted to be a biomarker of pathology such as seasonal depression or multiple sclerosis ( 42 , 72 ). Taken together it might be that various other processes related to opsin regulation have variable influence on changes in seasonal light responses.…”
Section: Discussionmentioning
confidence: 99%
“…One study looked at the pupillary light reflex in MS patients and found that attenuation of the melanopsin-mediated sustained pupillary constriction response was significantly associated with thinning of the GCIPL part of the retina, especially in patients with a history of acute ON [38].…”
Section: Pupillary Responsementioning
confidence: 99%
“…The PLR mediated by mRGCs has been investigated in different ophthalmological conditions including glaucoma (1618), retinitis pigmentosa (19), diabetes (20), Leber's congenital amaurosis (14), age-related macular degeneration (21), and ischemic optic neuropathies (22, 23). Moreover, various neurological and psychiatric disorders have been evaluated, including hereditary optic neuropathies (2429), seasonal affective disorder (SAD) (30), idiopathic intracranial hypertension (IIH) (31, 32), multiple sclerosis (MS) (33), and Parkinson's disease (PD) (34).…”
Section: Introductionmentioning
confidence: 99%